Proverbialité et traduction: la dichotomie forme-sens - Michaux, Christine (2017)
MICHAUX, Christine. Proverbialité et traduction: la dichotomie forme-sens. Revista de Letras, Fortaleza, v. 1, n. 36, p. 89-99, jan./jun. 2017.